Finite difference method and finite volume method for solving navier-stokes equation in sea water movement - Mohamed, Nur Syahida (2013)
This project proposed the Navier-Stokes equation of sea water modeling. The mathematical modeling consists of momentum , heat and salinity equations. The three parameters influence on sea water movement are momentum, temperature and salinity. The discretization of Navier-Stokes equation is based on Finite Difference Method (FDM) and Finite Volume Method (FVM ). The numerical methods for solving FDM are JB and GS schemes. The results are computed by using Comsol Multiphysics Software (4.3a) and MATLAB 2011a. The numerical analyses are used to evaluate the comparisons of the FDM and FVM. The computational platform is Intel"' Core IM 2 Duo processor T7500 memory. The aspects of evaluation are number of iteration, time execution, maximum error and root square error and com putational complexity. The results show that FDM is alternative method in visualizing the movement of the sea water